2011
DOI: 10.1158/0008-5472.can-11-0627
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Enhances Metastasis Formation via VEGFR-1–Expressing Endothelial Cells

Abstract: Recent studies suggest that chemotherapy, in addition to its cytotoxic effects on tumor cells, can induce a cascade of host events to support tumor growth and spread. Here, we used an experimental pulmonary metastasis model to investigate the role of this host response in metastasis formation. Mice were pretreated with chemotherapy and after clearance of the drugs from circulation, tumor cells were administered intravenously to study potential "protumorigenic" host effects of chemotherapy. Pretreatment with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
139
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 29 publications
11
139
0
1
Order By: Relevance
“…The host's response to several chemotherapy drugs has recently been investigated in various studies (11,25,26,(41)(42)(43). The first study reported that administration of cytotoxic-like vascular disrupting agents to non-tumor-bearing mice induced a rapid CEP mobilization (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host's response to several chemotherapy drugs has recently been investigated in various studies (11,25,26,(41)(42)(43). The first study reported that administration of cytotoxic-like vascular disrupting agents to non-tumor-bearing mice induced a rapid CEP mobilization (32).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously reported that chemotherapy induces molecular host factors that can contribute to tumor cell growth and tumor colonization in the lungs (11,(23)(24)(25)(26). For example, matrix metallopeptidase 9 (MMP9) secreted from bone marrow-derived cells (BMDC) that colonize paclitaxel-treated tumors may explain why mice primed with paclitaxel chemotherapy succumb to metastasis earlier than mice treated with vehicle control (25).…”
Section: Introductionmentioning
confidence: 99%
“…Daenen and colleagues showed that paclitaxel and cisplatin given to mice 4 days before intravenous tumor cell inoculation could lead to an upregulation of VEGFR-1 on endothelial cells, which, in turn, coincided with increased metastasis. Specific VEGFR-1 inhibitors were then shown to mitigate the treatment-mediated metastasis and extend survival (32).…”
Section: Mechanisms Of Timmentioning
confidence: 99%
“…For example, VEGFR-1 could be found on tumor cells of different tissue origin, where it promotes tumor growth rather than stimulates tumor angiogenesis (8). In animal tumor models, both VEGFR-1 and -2 are implicated in the development of established micrometastases (9); however, it is VEGFR-1 that is critically involved in the preparation of metastatic niche (10). In view of such differential involvement of VEGFR-1 and VEGFR-2 in the onset and progression of cancer, it would be logical to expect that each receptor might be an important biomarker for the selection of an appropriate cancer treatment or for monitoring the response to therapy in individual patients.…”
mentioning
confidence: 99%